2017
DOI: 10.1177/2325967117701882
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Joint Hypermobility Is Predictive of Hip Capsular Thickness

Abstract: Background:The pathomechanics of hip microinstability are not clearly defined but are thought to involve anatomical abnormalities, repetitive forces across the hip, and ligamentous laxity.Purpose/Hypothesis:The purpose of this study was to explore the relationship between generalized joint hypermobility (GJH) and hip capsular thickness. The hypothesis was that GJH would be predictive of a thin hip capsule.Study Design:Cross-sectional study; Level of evidence, 3.Methods:A prospective study was performed on 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 40 publications
(76 reference statements)
2
35
1
Order By: Relevance
“…4 The texture and elasticity of the hip capsule vary considerably between patients. 5,6 In those patients with hypermobility, the capsule is thin and stretchy, like spandex, whereas in those with stiffer tissues, it is more like sack cloth. 5 Second, arthroscopic surgery takes place under water.…”
Section: See Related Article On Page 471mentioning
confidence: 99%
See 2 more Smart Citations
“…4 The texture and elasticity of the hip capsule vary considerably between patients. 5,6 In those patients with hypermobility, the capsule is thin and stretchy, like spandex, whereas in those with stiffer tissues, it is more like sack cloth. 5 Second, arthroscopic surgery takes place under water.…”
Section: See Related Article On Page 471mentioning
confidence: 99%
“…5,6 In those patients with hypermobility, the capsule is thin and stretchy, like spandex, whereas in those with stiffer tissues, it is more like sack cloth. 5 Second, arthroscopic surgery takes place under water. As such, the tissue is continually absorbing the fluid that is pumped into the hip, which leads to engorgement as the case proceeds, thus altering not only its dimension but also its structural properties.…”
Section: See Related Article On Page 471mentioning
confidence: 99%
See 1 more Smart Citation
“…The joint laxity is evaluated using the Beighton score or the Brighton criteria for joint hypermobility syndromes. 9 These two tests are useful when examining athletes whose sport requires extreme hip range of motion maneuvers such as ballet dancers, gymnasts, figure skaters, martial artists, and others. 10 One study showed that patients with FAI have a higher prevalence of increased joint laxity.…”
Section: Diagnosis Of Fai In Athletes History and Physical Examinationmentioning
confidence: 99%
“…10 One study showed that patients with FAI have a higher prevalence of increased joint laxity. 9 In addition, a negative correlation has been reported between Beighton score and hip capsular thickness in patients who undergo primary hip arthroscopy for FAI. 9,11 Hip range of motion is evaluated in hip flexion, extension, internal rotation, external rotation, abduction, and adduction position (►Fig.…”
Section: Diagnosis Of Fai In Athletes History and Physical Examinationmentioning
confidence: 99%